Downes score as a clinical assessment for hypoxemia in neonates with respiratory distress - Anita Rusmawati; Ekawati L. Haksari; Roni Naning (Indonesian Pediatric Society Publishing House, 2016)
Background Hypoxemia in neonates with clinical respiratory distress has a high mortality. Downes score is used as an alternative to evaluate clinical respiratory distress if blood gas analysis instrument or pulse oxymetry is not available. Objective To evaluate the validity of Downes score for assessing hypoxemia in neonates with clinical respiratory distress. Methods A cross sectional study was carried out on neonates with clinical respiratory distress hospitalized at level 2 and 3 Neonatal Care Unit and in Emergency Room of Dr. Sardjito General Hospital, Yogyakarta. Downes score and oxygen saturation measured by a pulse oximetry were compared. Hypoxemia was defined as oxygen saturation less than 90% in term and post- term infants, less than 88% in preterm neonates, or Downes score 2:5 according to Basic Emergency Service Training for Obstetry and Neonatology (PONED) in 2007. The accuracy of Downes score in predicting hypoxemia was assessed by sensitivity, specificity, positive-predictive value, negative-predictive value, and likelihood ratio. Results Eighty nine neonates were evaluated. Downes score had sensitivity of 88%, specificity of 81 o/o, positive-predictive value of 72%, negative- predictive value of 92%, positive likelihood ratio 4.53, negative likelihood ratio 0.15, prevalence of 36%, and post test probability of 72%. Conclusion Downes score can be used as a clinical diagnostic means for assessing hypoxemia in clinical respiratory distressed neonates with 88% sensitivity (95% CI 79 to 99), and specificity 81% sensitivity (95% CI 70 to 91).